Adapting care for older cancer patients during the COVID-19 pandemic: Recommendations from the International Society of Geriatric Oncology (SIOG) COVID-19 Working Group. Issue 8 (November 2020) - Battisti, Nicolò Matteo Luca; Mislang, Anna Rachelle; Cooper, Lisa; O'Donovan, Anita; Audisio, Riccardo A.; Cheung, Kwok-Leung; Sarrió, Regina Gironés; Stauder, Reinhard; Soto-Perez-de-Celis, Enrique; Jaklitsch, Michael; Williams, Grant R.; O'Hanlon, Shane; et al.
Abstract: The COVID-19 pandemic poses a barrier to equal and evidence-based management of cancer in older adults. The International Society of Geriatric Oncology (SIOG) formed a panel of experts to develop consensus recommendations on the implications of the pandemic on several aspects of cancer care in this age group including geriatric assessment (GA), surgery, radiotherapy, systemic treatment, palliative care and research. Age and cancer diagnosis are significant predictors of adverse outcomes of the COVID-19 infection. In this setting, GA is particularly valuable to drive decision-making. GA may aid estimating physiologic reserve and adaptive capability, assessing risk-benefits of either providing or temporarily withholding treatments, and determining patient preferences to help inform treatment decisions. In a resource-constrained setting, geriatric screening tools may be administered remotely to identify patients requiring comprehensive GA. Tele-health is also crucial to ensure adequate continuity of care and minimize the risk of infection exposure. In general, therapeutic decisions should favor the most effective and least invasive approach with the lowest risk of adverse outcomes. In selected cases, this might require deferring or omitting surgery, radiotherapy or systemic treatments especially where benefits are marginal and alternative safe therapeutic options are available. Ongoing research is necessary to expand knowledge of the management of cancer in older adults. However, the pandemic presents a significant barrier and efforts should be made to ensure equitable access to clinical trials and prospective data collection to elucidate the outcomes of COVID-19 in this population.